Genome-Wide Enrichment Screening Reveals Multiple Targets and Resistance Genes for Triclosan in Escherichia coli - Yu, B.J., Systems and Synthetic Biology Research Center, KRIBB, Daejeon, Republic of Korea; Kim, J.A., Systems and Synthetic Biology Research Center, KRIBB, Daejeon, Republic of Korea; Ju, H.M., Systems and Synthetic Biology Research Center, KRIBB, Daejeon, Republic of Korea; Choi, S.K., Systems and Synthetic Biology Research Center, KRIBB, Daejeon, Republic of Korea; Hwang, S.J., LG Household and Healthcare Ltd., Daejeon, Republic of Korea; Park, S.Y., LG Household and Healthcare Ltd., Daejeon, Republic of Korea; Kim, E.J., GenoFocus Inc., Daejeon, Republic of Korea; Pan, J.G., Systems and Synthetic Biology Research Center, KRIBB, Daejeon, Republic of Korea (The journal of microbiology, 2012)
Triclosan is a widely used biocide effective against different microorganisms. At bactericidal concentrations, triclosan appears to affect multiple targets, while at bacteriostatic concentrations, triclosan targets FabI. The site-specific antibiotic-like mode-of-action and a widespread use of triclosan in household products claimed to possibly induce cross-resistance to other antibiotics. Thus, we set out to define more systematically the genes conferring resistance to triclosan; A genomic library of Escherichia coli strain W3110 was constructed and enriched in a selective medium containing a lethal concentration of triclosan. The genes enabling growth in the presence of triclosan were identified by using a DNA microarray and confirmed consequently by ASKA clones overexpressing the selected 62 candidate genes. Among these, forty-seven genes were further confirmed to enhance the resistance to triclosan; these genes, including the FabI target, were involved in inner or outer membrane synthesis, cell-surface material synthesis, transcriptional activation, sugar phosphotransferase (PTS) systems, various transporter systems, cell division, and ATPase and reductase/dehydrogenase reactions. In particular, overexpression of pgsA, rcsA, or gapC conferred to E. coli cells a similar level of triclosan resistance induced by fabI overexpression. These results indicate that triclosan may have multiple targets other than well-known FabI and that there are several undefined novel mechanisms for the resistance development to triclosan, thus probably inducing cross antibiotic resistance.